Exploring the Use of the "Quadratic Equation Board" Teaching Aid to Improve Seventh-Grade Students' Understanding of Quadratic - Maifalinda Fatra; Amrit Dhakal (Delta-Phi: Jurnal Pendidikan Matematika, 2024)
-This study aims to explore the impact of using the Quadratic Equation Board in improving seventh-grade students' understanding of quadratic equations through a qualitative research approach. Unlike previous studies that used experimental methods, this study relied on in-depth interviews, classroom observations, and document analysis to obtain a comprehensive overview of students' learning experiences and teachers' perceptions of the use of this innovative tool. Data were collected from students and teachersdirectly involved in the learning process using the Quadratic Equation Board. The results indicate that this tool can increase student engagement, facilitate understanding of the abstract concept of quadratic equations, and encourage active participation in classroom discussions. These findings emphasize the importance of integrating innovative learning media based on concrete teaching aids into mathematics lessons to create a more interactive and meaningful learning environment. This study recommends that mathematics teachers consider using similar tools to improve the quality of classroom instruction.